A Rare Cause of Upper Gastrointestinal Bleeding: Sarcina ventriculi. Issue 8 (31st August 2022) - Worrall, Emily B.; Chhaparia, Anuj; Carpenter, Danielle; Neuschwander-Tetri, Brent A.
ABSTRACT: We describe a patient who presented with hematemesis and was found to have unusually well-demarcated erythematous mucosa with a 2–3 cm irregular nonbleeding necrotic ulcer in the gastric body on esophagogastroduodenoscopy. Biopsy and pathologic examination of the tissue indicated infection with a rare bacterium, Sarcina ventriculi, prompting treatment with an unproven combination of 4 agents: metronidazole, ciprofloxacin, sucralfate, and pantoprazole. Repeat esophagogastroduodenoscopy 8 weeks later revealed complete resolution of the ulceration and surrounding erythema. These results may contribute toward establishing an appropriate therapeutic regimen for future S. ventriculi infections.